Development of a method to measure molecular frame EELS cross sections. (August 2015) - Watanabe, N; Yamada, S; Hirayama, T; Seki, A; Suzuki, D; Takahashi, M
Synopsis: We have developed an apparatus for electron-ion coincidence experiments to examine high-energy electron scattering cross sections in molecular frame. By using the apparatus a preliminary experiment is performed for inner-shell excitations of N2 at incident electron energy of 1.5 keV. The experimental result for the 1s → π * excitation clearly shows that the electron-scattering cross section for the fixed-in-space N2 molecule has successfully been obtained.